2010
DOI: 10.1186/1471-2164-11-468
|View full text |Cite
|
Sign up to set email alerts
|

Highly-multiplexed SNP genotyping for genetic mapping and germplasm diversity studies in pea

Abstract: BackgroundSingle Nucleotide Polymorphisms (SNPs) can be used as genetic markers for applications such as genetic diversity studies or genetic mapping. New technologies now allow genotyping hundreds to thousands of SNPs in a single reaction.In order to evaluate the potential of these technologies in pea, we selected a custom 384-SNP set using SNPs discovered in Pisum through the resequencing of gene fragments in different genotypes and by compiling genomic sequence data present in databases. We then designed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
120
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 56 publications
8
120
0
Order By: Relevance
“…With advances in model legume sequencing and genomic knowledge, there has been a switch to gene-based markers in pea (Aubert et al, 2006;Jing et al, 2007;Deulvot et al, 2010;Bordat et al, 2011). Recently, a comprehensive transcriptome of pea was published (Franssen et al, 2011), and another RNA-seq atlas is being established at INRA, France (http://bios.dijon.inra.fr).…”
Section: Impact Of Genomics For Crop Legumementioning
confidence: 99%
See 1 more Smart Citation
“…With advances in model legume sequencing and genomic knowledge, there has been a switch to gene-based markers in pea (Aubert et al, 2006;Jing et al, 2007;Deulvot et al, 2010;Bordat et al, 2011). Recently, a comprehensive transcriptome of pea was published (Franssen et al, 2011), and another RNA-seq atlas is being established at INRA, France (http://bios.dijon.inra.fr).…”
Section: Impact Of Genomics For Crop Legumementioning
confidence: 99%
“…Recently, a comprehensive transcriptome of pea was published (Franssen et al, 2011), and another RNA-seq atlas is being established at INRA, France (http://bios.dijon.inra.fr). This trend can be expected to further proliferate in conjunction with rapid advances in highthroughput single-nucleotide polymorphism (SNP) generation and detection assays (Deulvot et al, 2010;Bordat et al, 2011). In pea, a transcription atlas (RNAseq) and gene-based maps (Bordat et al, 2011) will aid translation of genomic knowledge to practical breeding.…”
Section: Impact Of Genomics For Crop Legumementioning
confidence: 99%
“…Krajevski et al (2012) used AFLP, RAPD, STS, CAPS and ISSR markers to localize QTL for yield components and protein content of two sets of recombinant inbred lines (RIL), reporting loci with consistent or inconsistent effects. Single nucleotide polymorphisms (SNP) have now become the preferred markers due to their abundance and uniform distribution throughout genomes (Gupta et al 2008), as confirmed by molecular linkage maps produced by Aubert et al (2006), Deulvot et al (2010), Duarte et al (2014) and Sindhu et al (2014). However, investigations on the linkage of SNP markers with pea production, phenology or grain quality traits are relatively few (Timmerman-Vaughan et al 2005;Burstin et al 2007;Klein et al 2014;Cheng et al 2015;Jha et al 2015), and the QTL ability to explain sufficient phenotypic variation for use in MAS is controversial.…”
mentioning
confidence: 99%
“…The objective of this study was to explore the ability of a standard set of SNP markers developed at INRA (Deulvot et al 2010;Carrillo et al 2014) to identify QTL for major agronomic and qualitative traits of pea in three connected bi-parental populations that were phenotyped in a spring-sown cropping environment of northern Italy. The three parent lines were elite varieties selected from a large number of recent cultivars on the grounds of high and stable grain yield across several Italian test environments (Annicchiarico 2005;Annicchiarico & Iannucci 2008).…”
mentioning
confidence: 99%
“…SNPs offer significant advantages relative to microsatellites such as lower error rates, the ability to combine and add to data overtime and space, a simple mutation model with low homoplasy and many technologies for high genotyping efficiency (Gupta, Roy, & Prasad, 2001;Vignal, Milan, SanCristobal, & Eggen, 2002;Batley, Mogg, Edwards, O'Sullivan, & Edwards, 2003;Morin et al, 2009). SNPs have been used as markers for genetic diversity studies, genetic mapping or population structure in plants (Deulvot et al, 2010;Foster et al, 2010;Inghelandt, Melchinger, Lebreton, & Stich, 2010).…”
Section: Introductionmentioning
confidence: 99%